2017
DOI: 10.1101/182691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SIN3A histone deacetylase complex is required for a complete transcriptional response to hypoxia

Abstract: Cells adapt to environmental changes, including fluctuations in oxygen levels, through the induction of specific gene expression programs. To identify genes regulated by hypoxia at the transcriptional level, we pulse-labeled HUVEC cells with 4-thiouridine and sequenced nascent transcripts. Then, we searched genome-wide binding profiles from the ENCODE project for factors that correlated with changes in transcription and identified binding of several components of the Sin3A co-repressor complex, including SIN3A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…FAM60A/SINHCAF is part of the SIN3A-HDAC complex, a master transcriptional repressor that is required for a complete response to hypoxia. 61 FAM60A/SINHCAF specifically represses HIF2a mRNA and protein expression by interacting with the TF SP1 and recruitment of HDAC1 to the HIF2a promoter. 62 HDAC7 is a class IIa histone deacetylase with a well described role in regulating angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FAM60A/SINHCAF is part of the SIN3A-HDAC complex, a master transcriptional repressor that is required for a complete response to hypoxia. 61 FAM60A/SINHCAF specifically represses HIF2a mRNA and protein expression by interacting with the TF SP1 and recruitment of HDAC1 to the HIF2a promoter. 62 HDAC7 is a class IIa histone deacetylase with a well described role in regulating angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GO analysis with the 70 genes associated to this 2641 differentially methylated sites, revealed that 26 genes and miRNAs are related to aging (Supplementary Table 1). Interestingly, some of them are directly or indirectly involved in chromatin remodeling (25), DNA damage response pathways (26), stress resistance (27) and longevity (28) and some miRNAs like mir125b-1 are preferentially expressed by skin stem cells regulating self-renewal and differentiation (29). Altogether, these results suggest strongly that our short induction protocol might improve the biological age of the skin through an epigenetically related mechanism.…”
Section: A Single Short Reprogramming Treatment Triggers Epigenetically Related Maintenance Of Skin Integritymentioning
confidence: 77%
“…Consequently, Sin3a was reported to be required for the development and/or survival of embryonic stem (ES) cells (11,12), muscle cells (13), male germ cells (14), lung progenitors (15), and some skin cells (16). In addition, gene expression and protein-DNA interaction studies showed that Sin3a could directly regulate molecules involved in cell proliferation, survival, metabolism, and stress responses (7,17,18), yet how Sin3a functions in postnatal organs has not been examined.…”
mentioning
confidence: 99%